Menilai Efektivitas Alat Pembelajaran Gamifikasi di Ruang Kelas Prasekolah - Moyo, Kgomotso; Safariningsih, Ratna Tri Hari; Baso, Farisha Andi; Sunanto, Sunanto (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
As digital technology becomes more embedded in early childhood education, gamified learning tools present a valuable opportunity to boost engagement and support cognitive development in preschool-aged children. This study explores the effectiveness of gamified tools in improving learning outcomes, motivation, and classroom participation among children aged 4 to 6 years. A mixed methods approach was used, involving two groups from preschools, the experimental group used gamified applications during instructional activities, while the control group followed traditional teaching methods over an eight-week period. Quantitative data were gathered through literacy and numeracy assessments conducted before and after the intervention, and qualitative data were collected through classroom observations and structured interviews with teachers. The findings revealed that children in the experimental group demonstrated statistically significant improvements in academic performance compared to the control group. They also showed higher levels of motivation, longer attention spans, and greater classroom engagement. Teachers reported more positive classroom dynamics during gamified sessions, noting increased enthusiasm, focus, and collaboration among students. These results suggest that gamified learning tools can serve as a powerful complement to traditional teaching approaches, helping to make early childhood education more effective and enjoyable. However, the study also emphasizes the importance of thoughtful implementation, such as aligning content with age-appropriate learning goals and ensuring teachers are well-equipped to facilitate technology-based instruction. Overall, gamified tools hold strong potential to enhance the preschool learning experience in meaningful ways.